Histological and stereological assessment of batch fecundity, spawning frequency and maturation of female Atlantic bluefin tuna around the Balearic Islands - Abascal F.J.; Megina C.; Medina A. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
The average batch fecundity of female eastern Atlantic bluefin tuna, Thunnus thynnus thynnus L., estimated from stereological quantification was of 92.8 oocytes per gram of body weight, and the spawning interval was calculated to be of 1.2 days. All the individuals from 3 years of age (19 kg of total body weight, 92 cm of fork length) showed mature ovaries, with migratory-nucleus ocytes and postovulatory follicles in most of the cases.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)